Engineering the Delivery System for CRISPR-Based Genome Editing. Issue 2 (February 2018) - Glass, Zachary; Lee, Matthew; Li, Yamin; Xu, Qiaobing
Abstract : Clustered regularly interspaced short palindromic repeat-CRISPR-associated protein (CRISPR-Cas) systems, found in nature as microbial adaptive immune systems, have been repurposed into an important tool in biological engineering and genome editing, providing a programmable platform for precision gene targeting. These tools have immense promise as therapeutics that could potentially correct disease-causing mutations. However, CRISPR-Cas gene editing components must be transported directly to the nucleus of targeted cells to exert a therapeutic effect. Thus, efficient methods of delivery will be critical to the success of therapeutic genome editing applications. Here, we review current strategies available for in vivo delivery of CRISPR-Cas gene editing components and outline challenges that need to be addressed before this powerful tool can be deployed in the clinic. Highlights: CRISPR is a novel gene editing tool that has the potential for multiple in vivo applications. Cas9 can target virtually any gene through complementarity to a synthetically produced gRNA. A major obstacle to in vivo implementation of CRISPR-mediated genome editing is an efficient, targeted delivery vehicle. Cas9 may be delivered to cells in DNA, mRNA, or protein format, and each mode has unique strengths, weaknesses, and delivery requirements. A variety of physical and chemical delivery vectors are available for Cas9 delivery.